ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN KEUNGGULAN BERSAING PADA RUMAH MAKAN PANGKEP BUDI UTOMO TIMIKA - Suci Neng Safitri; Cindy Astika Putri; Tri Apriyono (Jurnal Ekonomi dan Bisnis, 2024)
This study aims to determine the factors that determine competitive advantage at Pangkep Budi Utomo Timika Restaurant. The research method used in this study is a descriptive method. Data collection techniques are carried out by observation and questionnaires. The analysis instrument used is Confirmatory Factor Analysis (CFA). The results of this study indicate that all factors are confirmed as determining factors for the competitive advantage of Pangkep Budi Utomo Timika Restaurant, namely product, price, promotion, and place factors.